2019
DOI: 10.5740/jaoacint.19-0094
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Wheat, Rye, and Barley Gluten in Oat and Oat Products by ELISA RIDASCREEN® Total Gluten: Collaborative Study, First Action 2018.15

Abstract: demonstrated performance on oat matrices, which meets the criteria as specified in SMPR 2017.021. Data from in-house validation experiments are available as Annex B to this publication. W ith a prevalence of 0.4-1.2% of the population in Europe, North America, Australia, and the Middle East (1), celiac disease (CD) is considered to be one of the most common food hypersensitivities. CD is an immunemediated inflammatory disease of the upper small intestine in genetically predisposed individuals triggered by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…AOAC suggests low recovery rates of 60%, but the PWG feels that, in general, the recovery range should be between 80 and 120 %, which is in line with Abbott et al (161). With respect to LOD and LOQ, the three ELISAs under consideration perform well and meet the requirements (18)(19)(20)(21).…”
Section: Performance Criteriasupporting
confidence: 59%
See 3 more Smart Citations
“…AOAC suggests low recovery rates of 60%, but the PWG feels that, in general, the recovery range should be between 80 and 120 %, which is in line with Abbott et al (161). With respect to LOD and LOQ, the three ELISAs under consideration perform well and meet the requirements (18)(19)(20)(21).…”
Section: Performance Criteriasupporting
confidence: 59%
“…The results of the study showed recoveries ranging from 99 to 137% for wheat, rye and barley when analyzing defined validation materials (159,160) and relative reproducibility standard deviations from 10 to 53% for samples containing 10 mg/kg of gluten or higher. Following review by the AOAC Expert Review Panel for Gluten Assays, the method was adopted as AOAC Official Method First Action 2018.15 (21).…”
Section: Advances In Compliance Monitoring Of Gluten-free Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gluten content was obtained by multiplying the prolamin content by a factor of 2, as stated in the Codex ( 3 ). Homogeneity of selected samples (meatball, wheat, at 20 mg/kg of gluten) prepared to be homogeneous and inhomogeneous, respectively, was tested using ten replicates from different parts of the sample container according to standard procedures ( 16 ). Mean values, absolute standard deviations and relative standard deviations (RSD) were calculated for all quantitative results.…”
Section: Methodsmentioning
confidence: 99%